A viewpoint describing the American Society of Transplantation rationale to conduct a comprehensive patient survey assessing unmet immunosuppressive therapy needs. Issue 3 (13th December 2022) - Taber, David J.; Gordon, Elisa J.; Jesse, Michelle T.; Myaskovsky, Larissa; Peipert, John Devin; Jaure, Allison; George, Roshan; Fitzsimmons, William
Abstract: This viewpoint aims to "set the stage" and provide the rationale for the proposed development of a large‐scale, comprehensive survey assessing transplant patients' perceived unmet immunosuppressive therapy needs. Research in organ transplantation has historically focused on reducing the incidence and impact of rejection on allograft survival and minimizing or eliminating the need for chronic immunosuppressive therapies. There has been less emphasis and investment in therapies to improve patient‐reported outcomes including health‐related quality of life and side‐effects. Patient‐focused drug development (PFDD) is a new and important emphasis of the Food and Drug Administration (FDA) that provides a guiding philosophy for incorporating the patient experience into drug development and evaluation. The American Society of Transplantation (AST) Board of Directors commissioned this working group to prepare for the conduct of a comprehensive patient survey assessing unmet immunosuppressive therapy needs. This paper aims to describe the basis for why it is important to conduct this survey and briefly outline the plan for broad stakeholder engagement to ensure the information gained is diverse, inclusive, and relevant for advancing PFDD in organ transplant recipients.